set f = prodnorm ;
A1: for a, b being Element of [.0,1.] holds prodnorm . (a,b) = prodnorm . (b,a)
proof
let a, b be Element of [.0,1.]; :: thesis: prodnorm . (a,b) = prodnorm . (b,a)
prodnorm . (a,b) = a * b by ProdDef
.= prodnorm . (b,a) by ProdDef ;
hence prodnorm . (a,b) = prodnorm . (b,a) ; :: thesis: verum
end;
C1: for a, b, c being Element of [.0,1.] holds prodnorm . ((prodnorm . (a,b)),c) = prodnorm . (a,(prodnorm . (b,c)))
proof
let a, b, c be Element of [.0,1.]; :: thesis: prodnorm . ((prodnorm . (a,b)),c) = prodnorm . (a,(prodnorm . (b,c)))
A2: a * b in [.0,1.] by Lemma1;
A3: b * c in [.0,1.] by Lemma1;
prodnorm . ((prodnorm . (a,b)),c) = prodnorm . ((a * b),c) by ProdDef
.= (a * b) * c by
.= a * (b * c)
.= prodnorm . (a,(b * c)) by
.= prodnorm . (a,(prodnorm . (b,c))) by ProdDef ;
hence prodnorm . ((prodnorm . (a,b)),c) = prodnorm . (a,(prodnorm . (b,c))) ; :: thesis: verum
end;
D1: for a, b, c, d being Element of [.0,1.] st a <= c & b <= d holds
prodnorm . (a,b) <= prodnorm . (c,d)
proof
let a, b, c, d be Element of [.0,1.]; :: thesis: ( a <= c & b <= d implies prodnorm . (a,b) <= prodnorm . (c,d) )
B1: ( 0 <= a & 0 <= b ) by XXREAL_1:1;
assume ( a <= c & b <= d ) ; :: thesis: prodnorm . (a,b) <= prodnorm . (c,d)
then a * b <= c * d by ;
then a * b <= prodnorm . (c,d) by ProdDef;
hence prodnorm . (a,b) <= prodnorm . (c,d) by ProdDef; :: thesis: verum
end;
T1: 1 in [.0,1.] by XXREAL_1:1;
for a being Element of [.0,1.] holds prodnorm . (a,1) = a
proof
let a be Element of [.0,1.]; :: thesis: prodnorm . (a,1) = a
a * 1 = a ;
hence prodnorm . (a,1) = a by ; :: thesis: verum
end;
hence ( prodnorm is commutative & prodnorm is associative & prodnorm is monotonic & prodnorm is with-1-identity ) by ; :: thesis: verum